2017
DOI: 10.1186/s13229-017-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of executive function and theory of mind performance in relation to attention-deficit/hyperactivity symptoms in autism spectrum disorders

Abstract: BackgroundIndividuals with autism spectrum disorder (ASD) frequently demonstrate symptoms of attention-deficit/hyperactivity disorder (ADHD). Previous findings in children with ASD have suggested that these symptoms are associated with an impairment in executive function (EF) abilities. However, studies rarely considered this association within a single framework that controls for other related factors such as Theory of Mind (ToM) abilities and ASD symptoms.MethodsWe used structural equation modeling to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 103 publications
0
27
0
4
Order By: Relevance
“…It should be noted that ASD is a disorder that is highly comorbid with other neurodevelopmental disorders such as ADHD [Leitner et al, 2014]. Some research has suggested that the EF impairment may be related to comorbid ADHD symptoms and not ASD specifically [Hill et al, 2014; Lukito et al, ]. The inclusion of an ADHD group in future analyses might offer important insight into this distinction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that ASD is a disorder that is highly comorbid with other neurodevelopmental disorders such as ADHD [Leitner et al, 2014]. Some research has suggested that the EF impairment may be related to comorbid ADHD symptoms and not ASD specifically [Hill et al, 2014; Lukito et al, ]. The inclusion of an ADHD group in future analyses might offer important insight into this distinction.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced cognitive empathy is commonly associated with autism (e.g., Baron-Cohen, Leslie, & Frith, 1985;Lukito et al 2017;Deschamps et al, 2014;Sasson et al, 2013b). Autistic children often show delays in acquiring ToM and have marked difficulty with abstract perspective-taking tasks (Hamilton, 2009).…”
Section: Are Reduced Self and Other Understanding Aspects Of The Bap?mentioning
confidence: 99%
“…De acordo com a tabela 3, do conjunto de ações educacionais e pedagógicas investigadas no presente estudo, os seguintes itens foram aqueles que os 217 professores foram menos favoráveis (apoio < 50%): (i) diminuir estímulos distratores que comprometem a atenção e concentração do aluno (46%), (ii) fragmentar tarefas escolares e dar pausas breves entre as tarefas (47%) e (iii) usar estímulos como elogios para estimular bons comportamentos do aluno em sala de aula (50%). Alterações atencionais, seja por fácil distração, déficit de autorregulação do comportamento, déficit de controle inibitório ou foco exagerado da atenção são frequentemente observadas em crianças com TEA (PITZIANTI, D'AGATI, PONTIS et al, 2016;LAWSON, AYLWARD, WHITE, REES, 2015;KEEHN, WESTERFIELD, MÜLLER et al, 2017;LUKITO, JONES, PICKLES et al, 2017). De fato, o DSM-5 recomenda que quando há déficits atencionais e de hiperatividade/impulsividade característicos do transtorno de déficit de atenção/hiperatividade, deve ser considerada a possibilidade dessa condição clínica também ser diagnosticada junto com o TEA (APA, 2014).…”
Section: Santa Mariaunclassified